Understanding Graphic And Visual Aids - Ade Aini Nuran (BAHAS, 2016)
This study is aimed to understand how to read a graph and other visual aids. After learning about graph and the visual aids, the students are expected to be able to read a graph in a text and other visual aids. Further, they can make their own graph in telling something. The writer has two fold goals in creating graphics: 1. to make the data stand out on the page and 2. To make the data support the main purpose of the document as clearly and strongly as possible. Many technical pieces of writing have two main kinds of material: 1. Prose, the text or written part of the document and 2. Supporting graphic material. Keywords : Reading, Graphic, Charts, Visual